BIMBINGAN DAN KONSELING UNTUK PENGEMBANGAN REGULASI DIRI PADA REMAJA MELALUI MEDIA DAILY PLAN [GUIDANCE DAN COUNSELING FOR THE DEVELOPMENT OF SELF-REGULATION IN ADOLESCENTS THROUGH THE MEDIA DAILY PLAN] - Asrori, Moh. Mizan; Nurjannah, N (Perkumpulan Ahli Bimbingan Konseling Islam (PABKI) Indonesia, 2022)
This study aims to explore the guidance and counseling services of ALA clients who have problems in self-regulation by applying the daily plan method. The research method used is descriptive qualitative. The findings of this study are that by using the daily plan, ALA clients are able to develop self-regulation and do not remember past traumas they have experienced and can even accept and make peace with their past. In addition, this study also shows that the daily plan is one of the media that can develop adolescent self-regulation.